Perkembangan Untirta Tv Tahun 2008-2013 - Diana Mutiarani; Arif Permana Putra; Ana Nurhasanah (Reslaj : Religion Education Social Laa Roiba Journal, 2022)
This study aimed to determine the development of Untirta TV in 2008-2013. This research method is historical, includes heuristics (data collection), source criticism, interpretation, and historiography. Data collection techniques with interviews, observations, and documentation were carried out at Untirta TV. The results of this study indicate that the forerunner to the birth of Untirta TV campus community television in 2008 was community television as a laboratory facility for television broadcast production courses. Untirta TV aims to prepare human resources who excel in communication science and have academic insight to compete in the practical world in real life in society. In its development in 2009-2013, it went through a long process to obtain a broadcasting operation permit (IPP). In 2009 Untirta TV was inaugurated as a community television and was the first broadcast on electronic mass media screens, namely analog-based conventional television using Ultra High-Frequency transmitters. Furthermore, in 2010-2012 Untirta TV struggled to get a Broadcasting Operation Permit (IPP). In 2012 Untirta TV succeeded in obtaining the first stage of the Broadcasting Operation Permit (IPP) from the Ministry of Communication and Information, namely conducting a trial. one year for television broadcasts. Furthermore, in 2013, the trial period for the broadcasting license has ended. It can be extended once until a permanent broadcasting operation license (IPP) is obtained. In 2013, along with increasingly rapid technological developments, Untirta TV finally switched to using a new mass media, namely the online media YouTube. Untirta TV community television contributed to the field of education in 2009-2013, namely as a forum for the aspirations and information of the Untirta TV academic community that is educative by holding a program of activities both internal and external activities carried out by Untirta TV as a medium of communication for students of Sultan Ageng Tirtayasa University. Keywords: Progress, Community Television, Untirta TV, YouTube